Peran UKS dalam Meningkatkan Kesehatan Lingkungan Sekolah di SDN Cipondoh 06 Kota Tangerang - Putra, Sabillal Irfan Mulyana; Fitri, Indah Zianira; Alfiyani, Devi; Alfiyanita, Nadilla; Rahmawati, Rima (Lembaga Yasin AlSys, 2024)
Quality human resources are those who are physically and mentally healthy. Efforts to develop quality and healthy human resources include implementing School Health Programs (UKS). Based on observations of the school environment and interviews with six respondents, including the principal of SDN Cipindoh 06 Kota Tangerang and five fourth and fifth-grade students, the results showed that most aspects of health and cleanliness in the school environment met the established standards. However, some aspects, such as the school library, prayer room, and bathrooms, did not meet the requirements, whereas other aspects were generally satisfactory. The UKS room met the standards, and the facilities and infrastructure were adequate, as was the UKS implementation team. However, the UKS at SDN Cipindoh 06 Kota Tangerang has not been operating optimally due to several factors: the UKS supervisor has been reassigned, resulting in no current supervisor, insufficient teacher participation in UKS training, lack of support and training from the health center, and limited exposure to information about UKS management. Interviews revealed that the six respondents indicated that health education and services, such as health counseling, cleanliness drives, and immunizations, were implemented at the school, but UKS management had not been maximized. In conclusion, while most aspects are met, some areas still require improvement.